The Effect of Website-Based E-Learning on Learning Outcomes of Electrical Engineering Drawings for Students of SMKN 3 Tondano - Eka Priyana; Verico Kumakau (Department of Electrical Engineering Education, Faculty of Engineering, State University of Manado, 2023)
This study aims to determine the effect of website-based e-learning on student learning outcomes in Electrical Engineering Drawing Class X TITL SMK Negeri 3 Tondano. This type of research is truly experimental in the form of a pre-test and post-test-only control group design with a population of all students of class X TITL totalling 50 students, and the sampling technique is simple random sampling. The sample taken is 50 students consisting of 2 classes, each class consisting of 25 students. Documentation techniques and knowledge tests obtain research data. Documentation techniques are used to obtain data and information in the form of numbers, student learning outcomes, and knowledge tests given at the beginning (pre-test) and at the end of the meeting (post-test). The collected data were analyzed using descriptive statistics. The descriptive statistical analysis showed that the average student learning outcomes for the experimental class pre-test were 65.20, with a standard deviation of 7.83. The average pre-test student learning outcomes for the control class was 59.00, with a standard deviation of 9.57. For the post-test, the average student learning outcomes for the experimental class were 81.20 with a standard deviation of 8.93, and the average post-test student learning outcomes for the control class were 74.80 with a standard deviation of 8.35. There is a significant difference in student learning outcomes in the electrical engineering drawing subject between groups treated using conventional methods and groups treated using website-based e-learning in class X TITL students of SMK Negeri 3 Tondano.